If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6 + x = 11 Solving -6 + x = 11 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + x = 11 + 6 Combine like terms: -6 + 6 = 0 0 + x = 11 + 6 x = 11 + 6 Combine like terms: 11 + 6 = 17 x = 17 Simplifying x = 17
| (3xy)(-4x^2y)= | | -4(2x-3)+3x=32 | | f(-1)=3(-1)-9 | | 0.25(6+8)= | | 2a-9=6a+7 | | v=1/3*12*13 | | x(y/y-x)^2 | | v=1/3*12*13 | | 7x+10=-4 | | 0.25(6+8)= | | 7x+10=-4 | | (-4x^3)=(-5x^7) | | (-4x^3)=(-5x^7) | | 0.5x=0.5x+1 | | 63=7(10-x) | | 4x+6x=15+5 | | -7m+20=#17m-10 | | 4(6+2i)=24+8i | | -4/12 | | 58+5x+10+11x+2=180 | | (7+i)+13=7+(i+13) | | 0.25(6x+8)= | | -3(1+4.5)=-17.5 | | 7p+16=-26 | | (4+i)+(-4-i)=0 | | 14xy-21xy^2= | | 3x+25y=15 | | 3-2(4x+5)=3-8x+10 | | 8(3t+2)-60=60 | | 3x-25y=15 | | -4(2/-2)^2= | | -3(y+7)=56 |